Hubungan Asupan Makan Selama Pembelajaran Tatap Muka terhadap Status Gizi Anak Sekolah Dasar: Tinjauan Pustaka - Jessica Putri Anumpitan; Reni Zuraida; Syahrul Hamidi Nasution (CV. Jasa Sukses Abadi, 2023)
Since the COVID-19 outbreak was first discovered in Wuhan City, China, Indonesia has issued a policy to maintain social distance at the community level, so that the education sector diverts online learning. Online learning is learning using the internet network and handheld cellphones and computers as learning media. There are several models of online learning applications such as classroom, zoom, as well as whatsapp group. In the case of COVID-19 in Indonesia, children aged 5-12 years have an obese nutritional status with a diet often followed by weight gain and an increase in the frequency of sitting. This is caused by children's activities to stay at home and lead to the creation of a new lifestyle for children, namely a sedentary lifestyle. Parents also experience a dilemma in teaching their children during online learning because parents are not yet popular with distance learning using handheld cellphones or computers as learning media. Therefore, the SKB 4 Ministers also stipulate face-to-face learning because the pandemic has become endemic. During face-to-face learning in Indonesia, children aged 5-12 years have good nutritional status due to the activities of children who are able to return to activities outside the home such as returning to school. If food intake is balanced according to needs accompanied by the selection of the right food ingredients will give birth to good nutritional status. Food intake that exceeds the body's needs will cause excess weight and conversely food intake that is less than needed will cause the body to become thin and susceptible to disease.